Effect of Composition on the Properties of Silica Foam Produced by Slurry Method - Nor Zaidin, Puteri Nur Syafiqah; Ahmad, Sufizar (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study explores the fabrication of silica foam derived from rice husk-based silica for potential use in water filtration systems. Silica served as the primary material, while polyethylene glycol (PEG) and carboxymethyl cellulose (CMC) were employed as binders in the slurry formulation. The investigation focused on the influence of different silica compositions, specifically 45 wt.%, 50 wt.%, and 55 wt.% at a constant sintering temperature of 1200°C. The resulting foams were characterized through morphological analysis using Scanning Electron Microscopy (SEM), density and porosity measurements following ASTM C20 standards, and compressive strength testing in accordance with ASTM C773-88. Pore sizes ranged from 237.12 µm to 452.08 µm. Foam analysis revealed an inverse relationship between density and porosity. The optimal density (0.5591 g/cm³) was recorded at 50 wt%, while maximum porosity (69.61%) occurred at 45 wt.%. Compressive strength peaked at 55 wt.% (0.162 N/mm²), indicating sufficient mechanical integrity. The findings underscore the significance of slurry composition, curing, and application methods in achieving optimal structural and mechanical properties. Overall, the replication method proved effective in producing silica foams with promising characteristics for sustainable and efficient water filtration applications.